Immune response in glioma’s microenvironment - Chen Houminji; Li Ming; Guo Yanwu; Zhong Yongsheng; He Zhuoyi; Xu Yuting; Zou Junjie (Innovative Surgical Sciences, 2021)
Glioma is the most common tumor of the central nervous system. In this review, we outline the immunobiological factors that interact with glioma cells and tumor microenvironment (TME), providing more potential targets for clinical inhibition of glioma development and more directions for glioma treatment.